2023
DOI: 10.3389/fphar.2023.1103927
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of consolidation durvalumab after chemoradiation therapy for stage III non-small-cell lung cancer: a systematic review, meta-analysis, and meta-regression of real-world studies

Abstract: Background: The current review aimed to pool real-world evidence on the efficacy and toxicity of consolidation durvalumab for stage III unresectable non-small cell lung cancer (NSCLC) after curative chemoradiotherapy.Methods: PubMed, CENTRAL, ScienceDirect, Embase, and Google Scholar were searched for observational studies reporting the use of durvalumab for NSCLC till 12th April 2022. Twenty-three studies with 4,400 patients were included.Results: The pooled 1-year overall survival (OS) and progression-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…In the observational PACIFIC-R study, which follows NSCLC patients who received durvalumab consolidation therapy after chemoradiation, the median time to start of durvalumab from the end of RT was 56.0 days, with 30.1% of patients having started within 42 days ( 119 ). Median PFS was 21.7 months (95% CI, 19.1–24.5) and 2-year OS rate reached 71.2% (95% CI, 68.8–73.6) of patients, which align with another real-world study ( 120 ) and are even higher than outcomes observed in the intervention group in PACIFIC. Notably in the PACIFIC-R trial, 31.6% of patients were >70 years old at the time of inclusion and median PFS was similar among patients aged less than 70 years and those aged between 70 and 75 (22.8 and 22.4 months, respectively); however, it was shorter in patients over 75 (19.2 months).…”
Section: The Blood Values At the Time Of Immunotherapy Initiationsupporting
confidence: 81%
“…In the observational PACIFIC-R study, which follows NSCLC patients who received durvalumab consolidation therapy after chemoradiation, the median time to start of durvalumab from the end of RT was 56.0 days, with 30.1% of patients having started within 42 days ( 119 ). Median PFS was 21.7 months (95% CI, 19.1–24.5) and 2-year OS rate reached 71.2% (95% CI, 68.8–73.6) of patients, which align with another real-world study ( 120 ) and are even higher than outcomes observed in the intervention group in PACIFIC. Notably in the PACIFIC-R trial, 31.6% of patients were >70 years old at the time of inclusion and median PFS was similar among patients aged less than 70 years and those aged between 70 and 75 (22.8 and 22.4 months, respectively); however, it was shorter in patients over 75 (19.2 months).…”
Section: The Blood Values At the Time Of Immunotherapy Initiationsupporting
confidence: 81%
“…Drawing from real-world data, this meta-analysis demonstrates that the short-term efficacy and safety profile of durvalumab align with the findings reported in the PACIFIC trial. The consistency of these results reinforces durvalumab’s application as a means to enhance clinical outcomes for patients with unresectable stage III NSCLC [ 10 ]. However, it is crucial to note that these investigations explicitly excluded patients experiencing disease progression before commencing ICIs following radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 58%
“…In this systematic review, we aimed to provide an overall picture of the efficacy of all PD-1/PD-L1 inhibitors administered for all patients with stage III NSCLC and perform appropriate subanalyses according to the patient's histology, tumor PD-L1 expression levels, and timeline of therapy. Another systematic review highlighted the use of durvalumab as consolidation therapy after chemoradiation therapy in unresectable stage III NSCLC, 28 and the results are consistent with those of the PACIFIC trial. 7 This review provides evidence to support the previously reported benefits of consolidation therapy with a PD-L1 inhibitor after chemoradiation therapy when disease progression is not observed in stage III NSCLC and introduces the prospect of using PD-L1 inhibitors other than durvalumab, such as sugemalimab.…”
Section: Discussionmentioning
confidence: 64%